2023
DOI: 10.1002/advs.202302144
|View full text |Cite
|
Sign up to set email alerts
|

A Multifunctional Interlocked Binder with Synergistic In Situ Covalent and Hydrogen Bonding for High‐Performance Si Anode in Li‐ion Batteries

Jae Hyuk Hwang,
Eunji Kim,
Eun Young Lim
et al.

Abstract: Silicon has garnered significant attention as a promising anode material for high‐energy density Li‐ion batteries. However, Si can be easily pulverized during cycling, which results in the loss of electrical contact and ultimately shortens battery lifetime. Therefore, the Si anode binder is developed to dissipate the enormous mechanical stress of the Si anode with enhanced mechanical properties. However, the interfacial stability between the Si anode binder and Cu current collector should also be improved. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…It is worth noting that the slope of the line corresponds to the Warburg factor (eq 1, Experimental Section). 42 Based on the Warburg factor, we determined the Li + diffusion coefficient of the Si/POWPU and Si/PVDF anodes (eq 2, Experimental Section). 43 We confirmed that the Li + diffusion coefficient of the Si/POWPU anode (1.64 × 10 −12 ) was higher than that of the Si/PVDF (8.28 × 10 −13 ).…”
Section: Electrochemical Performance Of the Si/powpu Anodementioning
confidence: 99%
“…It is worth noting that the slope of the line corresponds to the Warburg factor (eq 1, Experimental Section). 42 Based on the Warburg factor, we determined the Li + diffusion coefficient of the Si/POWPU and Si/PVDF anodes (eq 2, Experimental Section). 43 We confirmed that the Li + diffusion coefficient of the Si/POWPU anode (1.64 × 10 −12 ) was higher than that of the Si/PVDF (8.28 × 10 −13 ).…”
Section: Electrochemical Performance Of the Si/powpu Anodementioning
confidence: 99%